A method for rapidly determining the presence of flocculant residues in water-washed sand

CN120214279BActive Publication Date: 2026-10-30GUANGDONG CHANGDA ENG TESTING CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202510276486.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-03-10
Publication Date
2026-10-30
Estimated Expiration
2045-03-10

AI Technical Summary

Technical Problem

[0005]①除了测定实验样品的TOCs含量,还需要配制不同浓度的聚丙烯酰胺溶液(至少5个不同浓度溶液),拟合确定和絮凝剂浓度之间的关系,从而推算出大致絮凝剂残留量,工作量大;②其需与自来水混合,并用清水搓洗再取洗砂水进行稀释,测定有机碳总含量,取得的溶液代表性欠佳;③在搓洗过程中无疑给数据和最终结果带来误差

Benefits of technology

[0040]本发明通过分别测定洗去小于0.075mm的颗粒的砂样品及待测砂样品浊度值为50NTU时的时间,以时间为指标,判定待测砂样品中絮凝剂残留的多少,从而确定其是否可以直接作为原料用于混凝土的制备中。本发明从节省时间、方便的角度,检测方法简单、可靠。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120214279B_ABST
    Figure CN120214279B_ABST
Patent Text Reader

Abstract

The application provides a detection method for quickly determining flocculant residues in washed sand, and belongs to the technical field of building material science detection. The detection method comprises the following steps: taking a sand sample to be detected, washing away particles smaller than 0.075 mm, adding water to the remaining sand sample to obtain a sand suspension, measuring the time T1 when the turbidity value is 50 NTU, taking another sand sample to be detected, stirring the sand sample in water to obtain a sand suspension to be detected, measuring the time T2 when the turbidity value is 50 NTU, when T2 is less than or equal to 0.8T1, it is determined that the sand sample to be detected contains too much flocculant residue and cannot be used as raw material for the preparation of concrete; when T2 is greater than 0.8T1, it is determined that the sand sample to be detected contains little flocculant residue and can be used as raw material for the preparation of concrete. The detection method provided by the application is simple and reliable from the aspects of time saving and convenience.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of building materials science testing technology, and in particular relates to a rapid detection method for determining flocculant residues in washed sand. Background Technology

[0002] Against the backdrop of increasingly scarce river sand, washed sand is widely used in construction, highway, railway, and water conservancy projects. To reduce the impact of adverse factors such as the MB value (methylene blue value), chloride ion content, and lightweight substances in washed sand on concrete, washing processes are commonly used in sand production. This washing process requires a huge amount of clean water; generally, 2-3 tons of clean water are needed per ton of sand, posing a significant demand on precious water resources, increasing costs, and causing considerable waste. Therefore, flocculants are widely used in the production of washed sand. Through the flocculation and accelerated sedimentation of impurities, flocculants greatly increase sand washing efficiency and save water. However, the application of flocculants leads to the problem of flocculant residue in washed sand. Although this residue is small, it has many adverse effects on the workability of concrete, such as reducing concrete encapsulation, increasing concrete viscosity, promoting cement paste settling, and causing paste-aggregate separation. If the residue is large, it will seriously affect the smooth construction of concrete. Therefore, there is an urgent need for a simple and effective method to detect the amount of flocculant residue in washed sand and to control the use of flocculants in the washed sand production process.

[0003] Currently, there are many patented methods for determining flocculant residues, such as:

[0004] Patent application CN 202210505591.2 measures the total organic carbon (TOCs) content in a flocculant aqueous solution using a TOC analyzer, and calculates the residual amount of flocculant accordingly. This method has the following problems:

[0005] ① In addition to determining the TOCs content of the experimental samples, it is also necessary to prepare polyacrylamide solutions of different concentrations (at least 5 different concentration solutions), fit and determine the relationship with the flocculant concentration, and thus estimate the approximate flocculant residue, which is a lot of work; ② It needs to be mixed with tap water, rubbed with clean water, and then diluted with the sand washing water to determine the total organic carbon content, resulting in a solution with poor representativeness; ③ The rubbing process undoubtedly introduces errors into the data and the final results.

[0006] The patent application with patent number CN 202311854147.2 first measures the fluidity of mortar prepared with flocculant solutions of different concentrations, then prepares mortar using the supernatant of the washed sand suspension to be tested and measures its fluidity, and fits the two to calculate the residual flocculant in the washed sand. This method has the following problems:

[0007] ① Preparing flocculant solutions of different concentrations and using these solutions to prepare mortar for flowability testing also presents a significant workload issue; ② The upper clear liquid of the water-washed sand suspension to be tested is not clearly defined, and the concentration of the solution will change with different heights and sedimentation times, thus different sampling methods will produce large errors; ③ Mortar flowability is measured by using a jump table to determine the spread of mortar with standard cement and standard sand. This method has poor sensitivity. Flocculants will cause cement slurry to settle and increase viscosity, but have little effect on the spread of mortar, thus it cannot accurately characterize the amount of flocculant residue.

[0008] Patent application CN 201911336311.4 measures the viscosity of cement paste by taking the supernatant of a sand solution and calculating the flocculant content using a fitting relationship between viscosity and residual flocculant. This method has the following problems:

[0009] ① The specific location of the obtained supernatant was not specified. The flocculant causes impurities to flocculate and settle. The flocculant concentration varies with the solution height and sedimentation time, therefore the sampling of the supernatant is highly random, leading to significant data deviation; ② The formula used in this method is y = 4.166E. -3 *exp(t3 / 1217.9)-4.157E -3 This is an empirical formula, not a scientific explanation of the relationship between viscosity and flocculant residue in this method. my country has a wide variety of sand types, and the type and effect of flocculants all affect this empirical formula, so its accuracy is not good.

[0010] Patent application CN 201910556852.1 uses a viscosity detection device to measure the viscosity of aqueous solutions of flocculants at different concentrations, performs linear fitting between viscosity and flocculant concentration, and then calculates the residual amount of flocculant in washed sand by measuring the viscosity of the test sample. This method has the following problems:

[0011] ① The representativeness of the sampling is still not good. The patent describes taking a small amount of the supernatant in a beaker to test the viscosity and angle of the water. The concentration of flocculant in the supernatant varies greatly with location, sandstone properties, adsorption properties, and gradation of the washed sand. ② The fitting formula lacks mathematical logic and universality, and has low accuracy. ③ The relevant detection devices for detecting the viscosity and angle of water are currently not accurate enough.

[0012] The patent application with patent number CN 202311148772.5 measures the peak area of ​​seven standard samples at different concentrations using liquid chromatography, plots a standard curve showing the relationship between the peak area and the concentration of the standard samples, and then calculates the concentration of the corresponding flocculant by detecting the peak area of ​​the sample being tested. However, this method also has the following problems:

[0013] ① Seven standard samples of different concentrations need to be tested, and a curve showing the change of peak area in liquid chromatography with polyacrylamide flocculants needs to be plotted, making the testing process quite cumbersome; ② The plotted curves are based on fitting relationships and lack universality and accuracy; ③ The extraction process of flocculants in washed sand lacks standard guidance and is not accurate enough.

[0014] Patent application number CN 202310540126.7 also proposes a detection device that uses the start-up time of the laser emitter and the trigger time of the photosensitive module to calculate the corresponding flocculant content data. This method also has the following problems:

[0015] In water-washed sand suspensions, the change in laser intensity transmitted through the solution is not only affected by flocculants. The mud content, light material content, saturated surface dry water absorption rate, lithology, and stone powder content will all have varying degrees of influence. Therefore, it is impossible to accurately show the correspondence between the laser intensity transmitted through the solution and the flocculant concentration. As a result, this method also has the problem of poor accuracy.

[0016] In summary, most existing technologies establish the relationship between flocculant concentration and concentration indirectly by preparing solutions with different flocculant concentrations, and then calculate the concentration of the sample being tested. This method has relatively low accuracy. The preparation of flocculants at different concentrations is significantly affected by the sandstone's properties and gradation. During sand washing, some flocculants are adsorbed into the sand, while only a portion dissolves in the solution. Furthermore, the gradation of washed sand varies. Washed sand with a higher content of fine particles has a larger specific surface area, allowing more flocculant to adhere to the particle surface, adhere to each other, and settle, resulting in a lower actual flocculant content in the aqueous solution.

[0017] This demonstrates that there are numerous types of flocculants available, and no simple, rapid, and effective method exists to detect their type and content. The harmful effects of flocculant residue on concrete are well-documented. my country pumps a massive volume of concrete annually, particularly in the Yangtze River Delta and Pearl River Delta regions where washed sand is commonly used. Therefore, a simple, effective, and practical method is urgently needed for both the quality control of flocculants themselves and their testing in washed sand applications.

[0018] Based on the above background, this invention proposes a method for rapidly determining flocculant residues in washed sand from a practical perspective. Summary of the Invention

[0019] To address the aforementioned technical problems, this invention proposes a rapid detection method for determining flocculant residues in washed sand, thereby enabling the monitoring and control of flocculant residues in washed sand.

[0020] To achieve the above objectives, the present invention provides a rapid detection method for determining flocculant residue in washed sand, comprising the following steps:

[0021] (1) Take the sand sample to be tested, wash away the particles with a diameter of less than 0.075 mm, wash the remaining sand sample with water and dry it to constant weight, add water and stir to obtain a sand suspension. Start timing when stirring stops, and measure the turbidity value at the center of the sand suspension 30 mm away from the liquid surface. When the turbidity value is 50 NTU, record the time T1.

[0022] (2) Take another sand sample to be tested, measure the water content of the sand sample to be tested to obtain the water content, then put the sand sample to be tested into water, stir to obtain the sand suspension to be tested, start timing when stirring stops, measure the turbidity value at the center of the sand suspension 30mm away from the liquid surface, and record the time T2 when the turbidity value is 50NTU.

[0023] (3) When T2≤0.8T1, it is determined that there is too much flocculant residue in the sand sample to be tested and it cannot be used as a raw material in the preparation of concrete; when T2>0.8T1, it is determined that there is little flocculant residue in the sand sample to be tested and it can be used as a raw material in the preparation of concrete.

[0024] Furthermore, in step (1), the mass ratio of the dried sand sample to water in the sand suspension is 1:3.

[0025] Further, in step (2), the mass ratio of the sand sample to water in the sand suspension is 1:(1-water content).

[0026] Further, in step (2), the moisture content of the sand sample to be tested is determined in accordance with the method in GB14684.

[0027] Furthermore, in both steps (1) and (2), the stirring time is 5 minutes.

[0028] Further, in step (1), the drying temperature is (105±5)℃.

[0029] Further, in step (1), the sand sample to be tested is mixed with water to form a suspension, and the suspension is passed through a 0.075mm sieve to wash away particles smaller than 0.075mm.

[0030] Furthermore, in step (1), the operation of washing away particles smaller than 0.075 mm is repeated at least twice.

[0031] The present invention also provides the application of the method for rapidly determining flocculant residue in washed sand in the preparation of concrete.

[0032] Furthermore, when T2 > 0.8T1, it is determined that there is little flocculant residue in the sand sample to be tested, and it can be used as a raw material in the preparation of concrete; when T2 ≤ 0.8T1, it is determined that there is too much flocculant residue in the sand sample to be tested. After washing away particles smaller than 0.075mm from the sand sample to be tested, it can be used as a raw material in the preparation of concrete.

[0033] For example, the present invention provides a method for rapidly determining flocculant residue in washed sand, specifically including the following steps:

[0034] (1) Take ≥2kg of the sample to be tested, and after manual quartering, take 500g and put it into a 3000mL beaker. Add 2000mL of distilled water and stir with an impeller at (600±60)r / min for 5min to form a suspension. Then, pass the prepared suspension through a 0.075mm sieve. Specifically, place the 0.075mm sieve into the suspension (so that the water level of the suspension is slightly higher than the upper surface of the sand particles in the sieve) and shake it back and forth to fully wash away particles smaller than 0.075mm. Then rinse the remaining fine particles on the sieve with distilled water.

[0035] After washing, the remaining sand sample was placed in a clean 3000mL beaker, and distilled water was poured into the beaker. The above operation was repeated at least twice to ensure that the water in the container was visually clear. Then, the sieved particles and the washed sample in the washing container were poured into an enamel dish and placed in an oven to dry at (105±5)℃ to constant weight. After cooling to room temperature (25±2℃).

[0036] (2) Weigh out 250g of dried sand sample, then put the 250g dried sand sample into a 2000mL beaker (the beaker size is: the diameter of the beaker body is 138±3mm and the height is 195±5mm), add 750g of distilled water, and stir with an impeller stirrer for 5min to obtain a sand suspension. Stop stirring and start timing. Immediately use a turbidimeter to measure the turbidity value at a distance of 30mm from the center of the liquid surface. Start observing the turbidity of the suspension. At the beginning, record the turbidity value every 10min. When the turbidity value is close to 100NTU, shorten the detection interval. When the turbidity value is 50NTU, record the time T1. Round the result to 1min.

[0037] (3) The water content of the sand sample to be tested was determined according to GB14684 to obtain the water content ω. Then, ≥2kg of the sample to be tested was taken, and 250g of the sand sample to be tested was placed in a 2000mL beaker after manual quartering. (750-250×ω)g of distilled water was added, and the sand suspension to be tested was prepared by stirring with an impeller mixer for 5min. The mixer was stopped and the timing was started. The turbidity value was measured at 30mm from the center of the liquid surface with a turbidity meter immediately. The turbidity of the suspension was observed. At the beginning, the turbidity value was recorded every 10min. When the turbidity value approached 100NTU, the detection interval was shortened. When the turbidity value was 50NTU, the time T2 was recorded. The result was rounded to 1min.

[0038] (4) When T2≤0.8T1, it is determined that there is too much flocculant residue in the sand sample to be tested and it cannot be used as a raw material in the preparation of concrete; when T2>0.8T1, it is determined that there is little flocculant residue in the sand sample to be tested and it can be used as a raw material in the preparation of concrete.

[0039] Compared with the prior art, the present invention has the following advantages and technical effects:

[0040] This invention determines the amount of flocculant residue in a sand sample by measuring the time it takes for a sand sample to wash away particles smaller than 0.075 mm and for the sand sample to reach a turbidity value of 50 NTU. This time is used as an indicator to determine whether the sand sample can be directly used as a raw material in concrete preparation. This invention offers a simple and reliable detection method that is time-saving and convenient. Attached Figure Description

[0041] The accompanying drawings, which form part of this invention, are used to provide a further understanding of the invention. The illustrative embodiments of the invention and their descriptions are used to explain the invention and do not constitute an undue limitation of the invention. In the drawings:

[0042] Figure 1 The effect of residual flocculant concentration on the turbidity of the washed sand solution 10 minutes after stirring stops;

[0043] Figure 2 The results show the effect of different concentrations of flocculant residue on the sedimentation time required when the turbidity of sand suspension is 50 NTU. Detailed Implementation

[0044] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as a limitation of the present invention, but rather as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0045] It should be understood that the terminology used in this invention is merely for describing particular embodiments and is not intended to limit the invention. Furthermore, with respect to numerical ranges in this invention, it should be understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. Every smaller range between any stated value or intermediate value within a stated range, and any other stated value or intermediate value within said range, is also included in this invention. The upper and lower limits of these smaller ranges may be independently included or excluded from the range.

[0046] Unless otherwise stated, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art. While only preferred methods and materials have been described herein, any methods and materials similar or equivalent to those described herein may be used in the implementation or testing of this invention. All references to this specification are incorporated by way of citation to disclose and describe methods and / or materials associated with those references. In the event of any conflict with any incorporated reference, the content of this specification shall prevail.

[0047] Various modifications and variations can be made to the specific embodiments described in this specification without departing from the scope or spirit of the invention, as will be apparent to those skilled in the art. Other embodiments derived from this specification will also be readily apparent to those skilled in the art. This specification and embodiments are merely exemplary.

[0048] The terms “include,” “including,” “have,” “contain,” etc., used in this article are all open-ended terms, meaning that they include but are not limited to.

[0049] This invention provides a rapid detection method for determining flocculant residue in washed sand, comprising the following steps:

[0050] (1) Take the sand sample to be tested, wash away particles smaller than 0.075 mm, wash the remaining sand sample with water and dry it to constant weight, add water and stir to obtain a sand suspension. Start timing when stirring stops, and measure the turbidity value at the center of the sand suspension 30 mm away from the liquid surface. When the turbidity value is 50 NTU, record the time T1.

[0051] (2) Take another sand sample to be tested, measure the water content of the sand sample to be tested to obtain the water content, then put the sand sample to be tested into water, stir to obtain the sand suspension to be tested, start timing when stirring stops, measure the turbidity value at the center of the sand suspension 30mm away from the liquid surface, and record the time T2 when the turbidity value is 50NTU.

[0052] (3) When T2≤0.8T1, it is determined that there is too much flocculant residue in the sand sample to be tested and it cannot be used as a raw material in the preparation of concrete; when T2>0.8T1, it is determined that there is little flocculant residue in the sand sample to be tested and it can be used as a raw material in the preparation of concrete.

[0053] In step (1) of the preferred embodiment of the present invention, the mass ratio of the dried sand sample to water in the sand suspension is 1:3.

[0054] In step (2) of the preferred embodiment of the present invention, the mass ratio of the sand sample to water in the sand suspension to be tested is 1:(1-water content).

[0055] In step (2) of the preferred embodiment of the present invention, the moisture content of the sand sample to be tested is determined in accordance with the method in GB14684.

[0056] In steps (1) and (2) of the preferred embodiment of the present invention, the stirring time is 5 minutes.

[0057] In step (1) of the preferred embodiment of the present invention, the drying temperature is (105±5)℃.

[0058] In step (1) of the preferred embodiment of the present invention, water is added to the sand sample to be tested and stirred to form a suspension. The suspension is then passed through a 0.075mm sieve to wash away particles smaller than 0.075mm.

[0059] In step (1) of the preferred embodiment of the present invention, the operation of washing away particles smaller than 0.075 mm is repeated at least twice.

[0060] This invention also provides the application of the method for rapidly determining flocculant residue in washed sand in the preparation of concrete.

[0061] In a preferred embodiment of the present invention, when T2 > 0.8T1, it is determined that there is little flocculant residue in the sand sample to be tested, and it can be used as a raw material in the preparation of concrete; when T2 ≤ 0.8T1, it is determined that there is too much flocculant residue in the sand sample to be tested, and after washing away particles smaller than 0.075mm in the sand sample to be tested, it can be used as a raw material in the preparation of concrete.

[0062] In this embodiment of the invention, 50 NTU represents the turbidity of water as 50 scattering turbidity units. NTU is an abbreviation for Nephelometric Turbidity Unit, which is used to measure the number and size of suspended particles in water, thereby reflecting the degree of turbidity. The higher the NTU value, the more suspended particles are in the water, and the less clear the water is.

[0063] The technical solution of the present invention will be further illustrated by the following embodiments.

[0064] Example 1

[0065] The mix proportion of pumped C30 concrete produced in a certain engineering practice is shown in Table 1. In Table 1, the cement is P·O42.5 cement; the fly ash is Class F, Grade II, with a fineness of 5.1%; the mineral powder is Grade 95 mineral powder; the sand is limestone manufactured sand with a fineness modulus of 2.8; the crushed stone is limestone with a particle size of 5-25mm; the admixture is standard polycarboxylate high-performance water-reducing agent with a water reduction rate of 28.0%; and the water is tap water.

[0066] Table 1 Mix proportions for pumped C30 concrete (kg / m³) 3 )

[0067] 260 70 70 165 830 1015 5.0

[0068] When pumped C30 concrete leaves the factory, the mixture is tested in accordance with GBT 50080-2016, and the performance test results are shown in Table 2.

[0069] Table 2 Results of Performance Testing for Pumped C30 Concrete

[0070]

[0071]

[0072] As can be seen from the data in Table 2, although the concrete prepared by directly using the sand in Table 1 meets the construction technical requirements of pumped concrete in terms of slump and spread, the viscosity of the mixture is relatively high, which results in a long emptying time of 12.9s in the slump cone, and a large slump loss. The initial setting time is also long, and the concrete appearance has defects such as exposed aggregate and poor encapsulation.

[0073] Therefore, this embodiment performs a rapid determination of flocculant residue in the washed sand used in Table 1, specifically including the following steps:

[0074] (1) Take 2.2 kg of sand sample to be tested, and after manual quartering, take 500 g and put it into a 3000 mL beaker. Add 2000 mL of distilled water and stir with an impeller mixer at (600±60) r / min for 5 min to form a suspension. Then, pass the prepared suspension through a 0.075 mm sieve. Specifically, put the 0.075 mm sieve into the suspension (so that the water level of the suspension is slightly higher than the upper surface of the sand particles in the sieve) and shake it back and forth to fully wash away particles smaller than 0.075 mm. Then rinse the remaining fine particles on the sieve with distilled water.

[0075] After washing, the remaining sand sample was placed in a clean 3000mL beaker, and distilled water was poured into the beaker. The above operation was repeated at least twice to ensure that the water in the container was visually clear. Then, the sieved particles and the washed sample in the washing container were poured into an enamel dish and placed in an oven to dry at (105±5)℃ to constant weight. After cooling to room temperature (25±2℃).

[0076] (2) Weigh out 250g of dried sand sample, then put the 250g dried sand sample into a 2000mL beaker (the beaker size is: the diameter of the beaker body is 138±3mm and the height is 195±5mm), add 750g of distilled water, and stir with an impeller mixer for 5min to obtain a sand suspension. Stop stirring and start timing. Immediately use a turbidimeter to measure the turbidity value at a distance of 30mm from the center of the liquid surface. Start observing the turbidity of the suspension. At first, record the turbidity value every 10min. When the turbidity value is close to 100NTU, shorten the detection interval. When the turbidity value is 50NTU, the recording time T1 = 720min.

[0077] (3) The water content of the sand sample to be tested was determined according to GB14684. The water content ω was 2.1%. Another 2.2 kg of the sample to be tested was taken and 250 g of the sand sample to be tested was placed in a 2000 mL beaker after manual quartering. (750-250×2.1%)=744.8 g of distilled water was added and stirred with an impeller mixer for 5 min to prepare the sand suspension to be tested. The mixer was stopped and the timing was started. The turbidity value was measured at 30 mm away from the center of the liquid surface with a turbidity meter immediately. The turbidity of the suspension was observed. At first, the turbidity value was recorded every 10 min. When the turbidity value approached 100 NTU, the detection interval was shortened. When the turbidity value was 50 NTU, the recording time T2=177 min;

[0078] (4) The results showed that T2 < 0.8T1, indicating that there was too much flocculant residue in the sand sample to be tested and it could not be used as a raw material in the preparation of concrete. Corresponding to the results in Table 2, the sand used in Table 1 could not be used as a raw material in the preparation of concrete.

[0079] Wash away particles smaller than 0.075 mm from the sand used in Table 1 according to the above steps (1) and dry the remaining particles. Prepare pumpable C30 concrete with the dried sand according to the proportions in Table 1 and test it in accordance with GBT 50080-2016. The performance test results are shown in Table 3.

[0080] Table 3. Results of Performance Testing of Freshly Mixed Pumped C30 Concrete

[0081]

[0082] Table 3 shows that a significant amount of flocculant residue in the sand significantly impacts concrete performance. Washing away particles smaller than 0.075 mm from the sand samples resolved this flocculant residue issue, resulting in improved physical properties of the prepared fresh concrete. (Admixture dosage: 5.0 kg / m³) 3 With the same amount of flocculant used, the slump and spread were increased, and the fluidity of the concrete was improved; the viscosity decreased from 12.9s to 10.2s, and the flow rate of the mixture increased; the slump loss and initial setting time were both reduced. Therefore, it was determined that the sand in Table 1 had too much residual flocculant and could not be used in the production of this concrete, which corresponds to the aforementioned conclusion.

[0083] It is evident that flocculant residue has a significant impact on the physical properties of fresh concrete, and there is an urgent need for a simple and rapid detection method to control flocculant residue in sand. The method described in this invention can be used to detect flocculant residue in sand simply and quickly.

[0084] Polyacrylamide flocculants were used to simulate flocculant residue in sand. The effect of different concentrations of flocculant residue on the sedimentation time required for a sand suspension with a turbidity of 50 NTU was studied. Washed sand solutions with flocculant concentrations of 0 mg / L, 1 mg / L, 5 mg / L, and 20 mg / L were prepared and stirred for 5 minutes using an impeller mixer to obtain sand suspensions. The timer started immediately after the mixer stopped, and the turbidity value was measured at a distance of 30 mm from the center of the liquid surface using a turbidimeter. The turbidity of the suspension was observed, initially recording the turbidity value every 10 minutes. When the turbidity value approached 100 NTU, the detection interval was shortened. The time was recorded when the turbidity value reached 50 NTU. The effect of the flocculant residue concentration on the turbidity of the washed sand solution 10 minutes after stirring stopped is shown in the figure. Figure 1 The effect of different concentrations of residual flocculant on the sedimentation time required for a sand suspension with a turbidity of 50 NTU is shown in the figure. Figure 2 .Depend on Figure 1 and Figure 2 It can be seen that the more flocculant residue there is, the shorter the required sedimentation time. Therefore, from the perspective of saving time and convenience, the detection method of the present invention is simple and reliable.

[0085] Example 2

[0086] The mix proportions of pumped C35 concrete produced in a certain engineering practice are shown in Table 4. In Table 4, the cement is P·O42.5 cement; the fly ash is Class F, Grade II fly ash, with a water requirement ratio of 98% and a fineness of 6.1%; the sand is manufactured granite sand with a fineness modulus of 2.7; the crushed stone is limestone with a particle size of 5-30mm; the admixture is a retarding polycarboxylate high-performance water-reducing agent with a water reduction rate of 29.5%; and the water is tap water.

[0087] Table 4 Mix proportions for pumped C35 concrete (kg / m³) 3 )

[0088] 280 100 164 837 1039 5.5

[0089] When pumped C35 concrete leaves the factory, the mixture is tested in accordance with GBT 50080-2016, and the performance test results are shown in Table 5.

[0090] Table 5. Results of Performance Testing for Pumped C35 Concrete

[0091]

[0092] As can be seen from the data in Table 5, the concrete prepared directly using the sand in Table 4 has several drawbacks, including insufficient coating, separation of cement paste and aggregate, high viscosity, long slump cone emptying time, significant slump loss, and a long initial setting time. This indicates that excessive residual flocculant in the washed sand leads to insufficient performance of the mixture.

[0093] Therefore, in this embodiment, the residual flocculant in the washed sand used in Table 4 was quickly determined and detected using the same method as in Example 1. The results showed that T1 = 682 min, T2 = 145 min, and T2 < 0.8T1. It was determined that there was too much residual flocculant in the sand sample to be tested, and it could not be used as a raw material for the preparation of concrete. Corresponding to the results in Table 5, the sand used in Table 4 cannot be used as a raw material for the preparation of concrete.

[0094] The sand used in Table 4 was washed to remove particles smaller than 0.075 mm using the same method as in Example 1, and the remaining particles were dried. The dried sand was then used to prepare pumpable C35 concrete according to the proportions in Table 4, and the concrete was tested in accordance with GBT 50080-2016. The performance test results are shown in Table 6.

[0095] Table 6. Performance Test Results of Freshly Mixed Pumped C35 Concrete

[0096]

[0097] As can be seen from Table 6, under the same mix proportion, the problem of flocculant residue can be solved by washing away particles smaller than 0.075 mm from the sand sample to be tested. The performance of the fresh concrete prepared is improved to varying degrees. Therefore, it is determined that the sand in Table 4 has too much flocculant residue and cannot be used in the production of this concrete, which corresponds to the aforementioned conclusion.

[0098] Example 3

[0099] The mix proportions of pumped C50 non-vibrating steel pipe concrete produced in a certain engineering practice are shown in Table 7. In Table 7, the cement is P·C42.5 cement; the fly ash is Class I F fly ash with a water requirement ratio of 92% and a fineness of 5.5%; the sand is manufactured granite sand with a fineness modulus of 2.9; the crushed stone is granite with a particle size of 5-25mm; the admixture is a retarding polycarboxylate high-performance water-reducing agent with a water reduction rate of 28.2%; and the water is tap water.

[0100] Table 7 Mix Proportion of Pumped C50 Non-Vibration Steel Pipe Concrete (kg / m³) 3 )

[0101] 420 50 162 739 1064 6.5

[0102] When pumped C50 non-vibrating steel pipe concrete leaves the factory, the mixture is tested in accordance with GBT 50080-2016, and the performance test results are shown in Table 8.

[0103] Table 8. Performance Test Results of Pumped C50 Non-Vibration Concrete in Steel Pipes

[0104]

[0105] Because the prepared concrete is high-grade, non-vibrating C50 concrete for steel pipes, it is required to fill the interior of the steel pipe with its own fluidity under pumping pressure to increase structural rigidity. Therefore, if the concrete's fluidity cannot meet the requirements, it is very easy to cause pipe blockage, resulting in the scrapping of the steel pipe concrete. As can be seen from the data in Table 8, the C50 concrete itself has a high viscosity, and the admixture dosage is relatively large, prolonging the setting time. It is difficult to determine whether this is due to the influence of flocculant residue.

[0106] Therefore, in this embodiment, the residual flocculant in the washed sand used in Table 7 was quickly determined and tested. The testing method was the same as in Example 1. The results showed that T1 = 420 min, T2 = 380 min, and T2 > 0.8T1. The residual flocculant in the sand sample was determined to be qualified and could be used as a raw material in the preparation of concrete.

[0107] The sand used in Table 7 was washed to remove particles smaller than 0.075 mm using the same method as in Example 1, and the remaining particles were dried. The dried sand was then used to prepare pumpable C50 non-vibrating steel pipe concrete according to the proportions in Table 7, and the concrete was tested in accordance with GBT 50080-2016. The performance test results are shown in Table 9.

[0108] Table 9. Performance Test Results of Freshly Pumped C50 Non-Vibrating Steel Pipe Concrete

[0109]

[0110] As can be seen from the data in Tables 8 and 9, the difference between the two data is small. Therefore, it is determined that the residual flocculant in the sand in this embodiment is qualified and can be used in the production and preparation of this concrete, which is consistent with the aforementioned conclusion.

[0111] Example 4

[0112] The mix proportion of C35 underwater cast-in-place pile concrete produced in a certain engineering practice is shown in Table 10. In Table 10, the cement is P·O42.5 cement; the fly ash is Class F Grade II fly ash with a water requirement of 99% and a fineness of 6.7%; the sand is river sand with a fineness modulus of 2.6; the crushed stone is limestone with a particle size of 5-20mm; the admixture is standard polycarboxylate high-performance water-reducing agent with a water reduction rate of 26.4%; and the water is tap water.

[0113] Table 10 C35 Underwater Cast-in-Place Pile Concrete Mix Proportion (kg / m²) 3 )

[0114] 300 60 160 830 1050 6.8

[0115] When the C35 underwater cast-in-place pile concrete leaves the factory, the mixture is tested in accordance with GBT 50080-2016, and the performance test results are shown in Table 11.

[0116] Table 11 Results of Concrete Performance Testing for C35 Underwater Cast-in-Place Piles

[0117]

[0118]

[0119] The C35 grade concrete used in underwater cast-in-place piles is designed for underwater applications. It requires good fluidity, the ability to self-flow and fill the bored pile, and good underwater anti-dispersion properties. As shown in Table 11, the residual flocculant resulted in insufficient concrete fluidity, leading to a slump cone emptying time of 13.7 seconds, increasing the risk of pile breakage.

[0120] Therefore, in this embodiment, the residual flocculant in the washed sand used in Table 10 was quickly determined and detected using the same method as in Example 1. The results showed that T1 = 630 min, T2 = 270 min, and T2 < 0.8T1. It was determined that there was too much residual flocculant in the sand sample to be tested, and it could not be used as a raw material in the preparation of concrete. Corresponding to the results in Table 11, the sand used in Table 10 cannot be used as a raw material in the preparation of concrete.

[0121] The sand used in Table 10 was washed to remove particles smaller than 0.075 mm using the same method as in Example 1, and the remaining particles were dried. The dried sand was then used to prepare C35 underwater cast-in-place pile concrete according to the proportions in Table 10, and the concrete was tested in accordance with GBT 50080-2016. The performance test results are shown in Table 12.

[0122] Table 12 Results of Performance Testing for Freshly Mixed C35 Underwater Cast-in-Place Concrete

[0123]

[0124] As can be seen from Table 12, under the same mix proportion, the problem of flocculant residue can be solved by washing away particles smaller than 0.075 mm from the sand sample to be tested. The performance of the fresh concrete prepared is improved to varying degrees. Therefore, it is determined that the sand in Table 10 has too much flocculant residue and cannot be used in the production of this concrete, which corresponds to the aforementioned conclusion.

[0125] Example 5

[0126] The mix proportion of C40 self-compacting concrete produced in a certain engineering practice is shown in Table 13. In Table 13, the cement is P·O42.5 cement; the fly ash is Class F II fly ash with a water requirement ratio of 99% and a fineness of 4.5%; the sand is manufactured granite sand with a fineness modulus of 2.8; the crushed stone particle size is 5-20mm; the admixture is standard polycarboxylate high-performance water-reducing agent with a water reduction rate of 27.8%; and the water is tap water.

[0127] Table 13 C40 Self-Compacting Concrete Mix Proportion (kg / m³) 3 )

[0128] 320 100 160 840 980 7.5

[0129] When C40 self-compacting concrete leaves the factory, the mixture is tested in accordance with GBT 50080-2016, and the performance test results are shown in Table 14.

[0130] Table 14 Results of Performance Testing for C40 Self-Compacting Concrete

[0131]

[0132]

[0133] C40 self-compacting concrete relies on its good fluidity and gravity to achieve compaction, resulting in high strength, fast construction speed, and good uniformity. However, as shown in Table 14, residual flocculant easily leads to insufficient concrete fluidity and a slow flow rate, resulting in a slump cone emptying time of 11.5 seconds. The concrete has high viscosity, a slow flow rate, and cannot achieve self-leveling, with a spread of only 480 mm.

[0134] Therefore, this embodiment uses the same method as in Example 1 to quickly determine the residual flocculant in the washed sand used in Table 13. The results show that T1 = 630 min, T2 = 180 min, and T2 < 0.8T1. It is determined that there is too much residual flocculant in the sand sample to be tested, and it cannot be used as a raw material for the preparation of concrete. Corresponding to the results in Table 14, the sand used in Table 13 cannot be used as a raw material for the preparation of concrete.

[0135] The sand used in Table 13 was washed to remove particles smaller than 0.075 mm using the same method as in Example 1, and the remaining particles were dried. The dried sand was then used to prepare C40 self-compacting concrete according to the proportions in Table 13, and the concrete was tested in accordance with GBT 50080-2016. The performance test results are shown in Table 15.

[0136] Table 15 Results of Performance Testing of Freshly Mixed C40 Self-Compacting Concrete

[0137]

[0138] As can be seen from Tables 14 and 15, the data differ significantly. Under the same mix proportion, the problem of flocculant residue can be solved by washing away particles smaller than 0.075 mm from the sand sample to be tested. The performance of the fresh concrete prepared is improved to varying degrees. Therefore, it is determined that the sand in Table 13 has too much flocculant residue and cannot be used in the production of this concrete, which corresponds to the aforementioned conclusion.

[0139] The above are merely preferred embodiments of the present invention, but the scope of protection of the present invention is not limited thereto. Any variations or substitutions that can be easily conceived by those skilled in the art within the scope of the technology disclosed in the present invention should be included within the scope of protection of the present invention. Therefore, the scope of protection of the present invention should be determined by the scope of the claims.

Claims

1. A rapid detection method for determining flocculant residue in washed sand, characterized in that, Includes the following steps: (1) Take the sand sample to be tested, add water to the sand sample to be tested and stir to form a suspension. Pass the suspension through a 0.075mm sieve to wash away particles smaller than 0.075mm. Repeat the operation of washing away particles smaller than 0.075mm at least twice. Wash the remaining sand sample with water and dry it to constant weight. Add water and stir to obtain a sand suspension. Start timing when stirring stops and measure the turbidity value at the center of the sand suspension 30mm away from the liquid surface. When the turbidity value is 50NTU, record the time T1. (2) Take another sand sample to be tested, measure the water content of the sand sample to be tested to obtain the water content, then put the sand sample to be tested into water, stir to obtain the sand suspension to be tested, start timing when stirring stops, measure the turbidity value at the center of the sand suspension 30mm away from the liquid surface, when the turbidity value is 50NTU, record the time T2, the mass ratio of the sand sample to water in the sand suspension to be tested is 1:(1-water content); (3) When T2≤0.8T1, it is determined that there is too much flocculant residue in the sand sample to be tested and it cannot be used as a raw material in the preparation of concrete; when T2>0.8T1, it is determined that there is little flocculant residue in the sand sample to be tested and it can be used as a raw material in the preparation of concrete.

2. The method for rapidly determining flocculant residue in washed sand according to claim 1, characterized in that, In step (1), the mass ratio of the dried sand sample to water in the sand suspension is 1:

3.

3. The method for rapidly determining flocculant residue in washed sand according to claim 1, characterized in that, In step (2), the moisture content of the sand sample to be tested is determined in accordance with the method in GB / T14684.

4. The method for rapidly determining flocculant residue in washed sand according to claim 1, characterized in that, In both steps (1) and (2), the stirring time is 5 minutes.

5. The method for rapidly determining flocculant residue in washed sand according to claim 1, characterized in that, In step (1), the drying temperature is (105±5)℃.

6. The application of the rapid detection method for determining flocculant residue in washed sand as described in any one of claims 1-5 in the preparation of concrete.

7. The application according to claim 6, characterized in that, First, the sand to be tested is tested using the detection method described in any one of claims 1-5. When the test result shows T2 > 0.8T1, it is determined that there is little flocculant residue in the sand sample and it can be used as a raw material in the preparation of concrete. When T2 ≤ 0.8T1, it is determined that there is too much flocculant residue in the sand sample. After washing away particles smaller than 0.075mm from the sand sample, it can be used as a raw material in the preparation of concrete.

Citation Information

Patent Citations

  • Method for detecting flocculant in sand and detecting device thereof

    CN110261265A

  • A method for detecting flocculants in sand

    CN111157403B

  • Method for detecting residual amount of flocculating agent in machine-made sand

    CN114994298A

  • A method and device for detecting flocculant content in sand

    CN116577278B

  • Method for detecting flocculant residues in machine-made sand

    CN117368339A